Peningkatan Hasil Belajar Siswa melalui Model PBL pada Materi Menghargai Hak Milik Orang Lain - Sinta Sitinjak (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve students' learning outcomes in the topic "Respecting Other People's Property" through the implementation of the Problem Based Learning (PBL) model in Class IV, Phase B of SD Negeri 03 Rantau Selatan. The background of this research stems from the observation that students' understanding and behavior related to respecting the property rights of others is still relatively low. This condition has directly impacted their learning outcomes, which have not yet met the Minimum Completion Criteria (KKM). The Problem Based Learning model was chosen because it emphasizes student-centered learning through the exploration of real-life problems. It is believed that this approach can foster students’ critical thinking, collaboration, and problem-solving skills, while also helping them connect learning materials with everyday situations that they can relate to. The method used in this study is Classroom Action Research (CAR), which is carried out in two cycles. Each cycle involves four stages: planning, implementation, observation, and reflection. Data were collected through various instruments including observation sheets, learning outcome tests (to measure cognitive development), and documentation (to support the analysis process). The results of the research indicate a significant improvement in students' learning outcomes after the application of the PBL model. This improvement is evident both in the cognitive domain, such as understanding of the material, and in the affective domain, such as changes in students’ attitudes and behavior in respecting others’ belongings. Based on these findings, it can be concluded that the Problem Based Learning model is effective and recommended for use in character-based education, particularly in strengthening students' understanding and appreciation of social values in daily life.